STRATEGI KOMUNIKASI UNGKAPAN PERMOHONAN OLEH MAHASISWA PENDIDIKAN BAHASA JEPANG TINGKAT III TAHUN 2014 UNIVERSITAS RIAU - Puteri, Gebby Dwi; Nimashita, Hana; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study identified the form of request expression, communication flow, and communication strategies which were used by the third grade students of Japanese Language Education Study Program University of Riau by doing roleplay as an instrument. This study used qualitative descriptive method. The data were obtained by using Simak Bebas Libat Cakap Technique and Record Technique. The theories used in this study are the Theory of Request Expressions in Japanese which is in the Minna no Nihongo Shokkyu I and II (1998), the Theory ofÂ Request Expressions in Japanese which was initiated by Kaiser (2000), the Theory of Communication Flow by Shirou (2008), and the Theory of Communication Strategies by Yule (2006). The result of this study indicates 20 data of studentâ€™s conversation which contain the form of request expression and communication strategies. The most used form of request expressions are te moraemasenka and te kudasai. The used communication flow that likely to used is the students say foreword (maeoki) and directly stated reason (riyuu) without express apology (shazai). After that the students add a backup plan (daian). While in communicataion strategy, the most used communication strategy is negative politeness strategy.Â Keywords : Communication Strategies, Request Expressions, Communication Flow, Roleplay